2023
DOI: 10.4103/jfmpc.jfmpc_1200_22
|View full text |Cite
|
Sign up to set email alerts
|

A study on psychiatric conditions in children with school refusal- A clinic based study

Abstract: A BSTRACT Introduction: School refusal is a broad term that encompasses a child-motivated refusal to attend or remain at school, or a clear and apparent difficulty in doing so. Different factors that may influence the development of school refusal include a genetic predisposition, the home and family environment, the school environment, and social pressures. the present study aimed at examining, the psychiatric diagnostic status of children and adolescents who presented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…In a recent study, the prominent psychiatric co‑morbidities in such cases were unspecified childhood emotional disorder, separation anxiety, conversion disorder, over‑anxiety disorder, and somatoform disorder. 16 Previous studies have shown that children with complaints of school refusal generally present with anxiety symptoms, and teenagers have symptoms related with anxiety and mood disorders. 17 Some studies have highlighted mental retardation and learning difficulties as precursors to school refusal behavior.…”
Section: School Refusal: Key Conceptsmentioning
confidence: 99%
“…In a recent study, the prominent psychiatric co‑morbidities in such cases were unspecified childhood emotional disorder, separation anxiety, conversion disorder, over‑anxiety disorder, and somatoform disorder. 16 Previous studies have shown that children with complaints of school refusal generally present with anxiety symptoms, and teenagers have symptoms related with anxiety and mood disorders. 17 Some studies have highlighted mental retardation and learning difficulties as precursors to school refusal behavior.…”
Section: School Refusal: Key Conceptsmentioning
confidence: 99%
“…This means that a specialist doctor must conduct an examination and prescribe tests. If a psychosomatic reaction becomes a habitual way of reacting to stress, then consultation with a neurologist or psychotherapist is necessary (Biswas and Sahoo, 2023).…”
Section: Physiological Factorsmentioning
confidence: 99%